MANAJEMEN PENGASUHAN ANAK DALAM KELUARGA - Nuraini Nuraini; Suryani Suryani (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
Parenting in a family that demands extra management of both energy, time, and material. This paper tries to discuss the management carried out by parents in aspects of time management, family, work, and parenting as well as financial management in the family. “Management is the whole process of cooperation between two or more parents based on a certain rationality to achieve predetermined goals. The realization of the ideal family or Islamic family is certainly everyone's dream. Islam has given special rules for husbands and wives to carry out leadership responsibilities in the household. The husband is the head and leader of the family, while the wife is the leader of the house as well as the leader for their children. begins by identifying the tasks, dividing the work according to ability, and focusing on what is being done. As for financial management, it is necessary to make a monthly budget so that there is no waste of family finances. Meanwhile, management in parenting children needs to understand and strive to be good listeners, calm and honest, communicative conversations, avoid barbaric questions, and provide motivation.